2019
DOI: 10.3390/molecules24091726
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Antagonism of Epigallocatechin-3-gallate in the Treatment of Digestive Tract Tumors

Abstract: Due to changes in the dietary structure of individuals, the incidence of digestive tract tumors has increased significantly in recent years, causing a serious threat to the life and health of patients. This has in turn led to an increase in cancer prevention research. Many studies have shown that epigallocatechin-3-gallate (EGCG), an active ingredient in green tea, is in direct contact with the digestive tract upon ingestion, which allows it to elicit a significant antagonizing effect on digestive tract tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 127 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…Among catechins, EGCG from green tea is one of the most studied, and it has been reported to be active against many types of cancer, including colorectal [31], lung [32], breast [33] and liver [34]. These effects basically arise from its abilities to promote pro-apoptotic effects, inhibit angiogenesis, regulate cellular metabolic pathways, and reduce inflammatory factors [28,35]. EGCG can increase the activities of traditional anticancer treatments [36][37][38] and reverse drug cell resistance, and this has encouraged its use in clinical trials for treatments of various types of cancer and other diseases [39].…”
Section: Discussionmentioning
confidence: 99%
“…Among catechins, EGCG from green tea is one of the most studied, and it has been reported to be active against many types of cancer, including colorectal [31], lung [32], breast [33] and liver [34]. These effects basically arise from its abilities to promote pro-apoptotic effects, inhibit angiogenesis, regulate cellular metabolic pathways, and reduce inflammatory factors [28,35]. EGCG can increase the activities of traditional anticancer treatments [36][37][38] and reverse drug cell resistance, and this has encouraged its use in clinical trials for treatments of various types of cancer and other diseases [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, a series of toxic side effects are induced by high doses of EGCG ( 30 ). Previous clinical studies have identified that the side effects of EGCG include nausea, insomnia and hepatotoxicity ( 31 , 32 ). When the present study was conducted, to the best of the authors' knowledge there were no previous studies in the literature to check the optimal EGCG concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) is a major polyphenolic constituent derived from green tea and has significant anticarcinogenic, antioxidant, anti-inflammatory, and neuroprotective properties [ 6 ]. Extensive research on EGCG has brought into light their potential to prevent cancer by inducing apoptosis and suppressing cell proliferation, migration, and invasion [ 7 , 8 ]. In addition, it has been reported that EGCG can protect vascular endothelial cells from oxidative stress-induced damage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%